The city as perpetual beta: fostering systemic urban acupuncture. - Fredericks, Joel; Caldwell, Glenda Amayo; Foth, Marcus; Tomitsch, Martin (Springer Open, 2019)
Applying the concept of perpetual beta to cities proposes a continual and never complete process of city-making. Building on this notion, this chapter employs a conceptual framework of urban acupuncture for conducting and analysing localised small-scale community engagement activities through situated pop-up interventions. Pop-up interventions 'hack' public space by temporarily changing the feel of a place to promote awareness around civic issues. The authors argue that the use of situated pop-up interventions has the potential to provide more inclusive forms of community engagement by combining digital and physical media. The proposed framework employs pop-up activism to facilitate a middle-out approach that encourages citizens to actively identify topics for discussion. Two pop-up interventions in different locations in Australia are discussed in the chapter to assess in what way a systemic level of impact can arise from different processes of city hacking that are facilitated through a distributed, decentralised, yet concerted and regular local approach. The authors argue that a concerted process of implementing small urban interventions can contribute to an ongoing commitment to participatory city-making. Further work will show how each local intervention can contribute to translating the notion of perpetual beta into systemic change beyond the boundaries of their individual locale and -taken together- across different urban environments of the city.
Keywords: Stadtsoziologie; Digitalisierung; Informationstechnologie; Partizipation; Stadtgesellschaft; Stadtsystem; Stadtgestaltung; Interaktion